Predictors of life satisfaction among Iranian undergraduate students in Malaysian private universities - Nabavi, Razieh Tadayon (2014)
Throughout the ages, education has often been considered the fruits of a good life and happiness, a life that is well lived (Arani & Abbasi, 2008). In recent years, many young people have gone abroad to study and they have to live at least temporarily in new countries that are not the same as their home. Some studies have shown that many indicators can affect these students‘ life satisfaction. Thus, the aim of this study was to determine the predictors of life satisfaction among Iranian undergraduates who are studying in Malaysian private universities. A total of 361 undergraduates who are studying in three universities (Multimedia University, University College Sedaya International, and Asia Pacific University of Malaysia) were identified as respondents of this study by using Multi-Stage random sampling technique. Data were collected through a survey technique using self-administered questionnaire. In this study, each respondent‘s social support, adjustment, loneliness, career readiness , and life satisfaction were measured by the Multidimensional Scale of Perceived Social Support (MSPSS; Zimet, Dahlem, Zimet, & Farley, 1988), the Student Adaptation to College Questionnaire (SACQ; Baker, Siryk, & Services, 1999), the revised Loneliness Scale University of California, Los Angeles (UCLA; D. Russell, Peplau, & Cutrona, 1980), the Career Factor Inventory (CFI; Chartrand, Robbins, Morrill, & Boggs, 1990), and The Satisfaction With Life Scale (SWLS; Diener, Emmons, Larsen, & Griffin, 1985) respectively. Data were analyzed using the descriptive and bivariate statistics such as, Pearson‘s correlation, Independent t-test and Multiple Regressions. The results of the study showed that the Iranian undergraduates in Malaysia were moderately satisfied with their life. Findings from Pearson‘s Product-Moment Correlation analyses revealed that social support, adjustment, academic achievement, and parent‘s income were positively related with life satisfaction, while there was a negative correlation between loneliness and life satisfaction. Independent t-test analysis revealed that there was no significant difference in life satisfaction among male and female Iranian undergraduates. Furthermore, the results of the multiple regression analyses indicated that social support emerged as the strongest unique predictor of life satisfaction, followed by academic achievement, and adjustment. A total of 44.8% of the variability in life satisfaction could be predicted by social support, academic achievement, and adjustment. The results also indicated that social support significantly mediated the effect of loneliness on life satisfaction. Theoretically, the findings may shed light on the role of social support in predicting undergraduates‘ life satisfaction particularly for Iranian undergraduates who are studying abroad. From a practical perspective, the findings may imply that any effort to enhance life satisfaction for undergraduates studying abroad would be more effective if the relevant authorities such as the Iranian Embassy or the university take initiative in organizing social support and academic achievement program for them.